An Augmented Counseling Approach on Fear of Crime and Self-Efficacy in Older Adults - Sanders, Margaret Perry (East Carolina University, 2022)
Fear of crime research notes two strong predictors of fear are fear of crime and perceived risk of victimization. Adults 65 years of age and older report a higher fear of crime than younger age groups. The effects of fear of crime on older adults can be long-lasting and have a notable impact on their mental, emotional, and physical wellbeing (National Center for Victims of Crimes, 2012; Tan and Haining, 2016; Rivara et al., 2019; Serfaty et al., 2016; Serfaty et al., 2021; Sheppard et al., 2021; Victims of Crime, 2019). Fear of crime models denotes a reciprocal nature to fear of crime impacting an individual's thoughts, behaviors, and actions (Rader et al., 2007; Rader, 2010; Rader, 2017). Social Cognitive Theory's triadic causation model further declares personal factors influencing an individual's behavior, environment, and vice versa (Bandura, 1989). One of the ways to promote positive behavioral change is by raising a person's perceived self-efficacy (Bandura, 1986; Bandura, 1990; Bandura, 2004). Raising an older adult's self-efficacy beliefs on successfully thwarting or dealing with an unsafe situation can be vital to countering fear of crime. Psychoeducation group counseling and self-defense training are common treatment modalities used to raise a person's self-efficacy in addressing fear of crime (Clark, 1998; Helgeson, Lepore, and Eton, 2006; Ozer & Bandura, 1990; Sanders & Murray, 2018). Both treatment approaches are often used separately to manage an individual's fear of crime. The present study compared an augmented group intervention (i.e., psychoeducation group counseling and self-defense training) to a non-augmented (i.e., psychoeducation group-only) group intervention on self-efficacy and fear of crime. A total of 34 older adults with a mean age of 68.21 years, primarily female, married or widowed, and retired, participated in the study. Participants were randomly assigned to an augmented or non-augmented group and provided the intervention remotely online, once a week for six weeks. Participants were measured on perceived self-efficacy, fear of crime, and perceived risk of crime pre and post the study. Participants in the augmented intervention were also measured on self-defense proficiency (i.e., pre and post-study). Participants were also asked to complete a weekly check-in survey and a satisfaction and technology questionnaire post the study. An RM ANOVA analysis revealed that the augmented and non-augmented groups increased perceived self-efficacy from engaging in the six study. An RM ANOVA also showed that the augmented group decreased in total fear of crime while the non-augmented group increased in fear. A simple linear regression showed that perceived self-efficacy did not predict total fear of crime. However, a regression analysis revealed self-defense self-efficacy was a predictor of total fear of crime for the augmented group. A paired-samples t-test showed the augmented group's self-defense proficiency in skill increased over time from engaging in the six-week study. Participants of both groups reported high to moderately-high satisfaction with the study design, remote online approach, and use of technology. Participants also indicated that participation in the study positively impacted their views of safety and self-defense. Future research would benefit from providing a similar study in person, developing instruments specific to measuring older adults' self-efficacy and fear of crime, and examining messages and message sources on fear of crime.
Keywords: group counseling; Fear; Self Efficacy; Crime; Counseling